An eHealth insomnia intervention for children with neurodevelopmental disorders: Results of a usability study. (March 2020) - Tan-MacNeill, Kim M.; Smith, Isabel M.; Weiss, Shelly K.; Johnson, Shannon A.; Chorney, Jill; Constantin, Evelyn; Shea, Sarah; Hanlon-Dearman, Ana; Brown, Cary A.; Godbout, Roger; Ipsiroglu, Osman; Reid, Graham J.; et al.
Highlights: Insomnia treatment is needed for children with neurodevelopmental disorders (NDD). Better Nights, Better Days (BNBD) is an eHealth program for typically developing children. Parents of children with NDD reported BNBD was usable, feasible, and acceptable. Parents' main recommendation was to add some diagnosis-specific information and strategies. Results largely support a modular transdiagnostic approach to insomnia treatment. Abstract: Background: Sleep problems, particularly insomnia, are highly prevalent in children with neurodevelopmental disorders (NDD) and can negatively affect health and development. eHealth interventions may increase access to evidence-based care for insomnia for children with NDD, as programs are rare in most communities. Better Nights, Better Days (BNBD) is an online, parent-implemented intervention for pediatric insomnia in typically developing 1- to 10-year-olds. Aims: The present study examined whether parents of children with NDD perceived the original BNBD to be usable, acceptable, and feasible, and what modifications might be necessary to adapt it for children with NDD. Methods and procedures: Twenty Canadian parents/caregivers of children aged 4–10 years with NDD and insomnia implemented the BNBD intervention with their children, and completed usability questionnaires. Questionnaire data were analyzed quantitatively (descriptive statistics) and qualitatively (thematic analysis). Outcomes and results: Participants reported the intervention to be usable, useful, acceptable, and feasible. Several modifications were suggested to make the intervention more appropriate and acceptable for use with children with NDD. Conclusions and implications: Results support a largely transdiagnostic approach to treating sleep in children with NDD, and will inform the development of BNBD for Children with Neurodevelopmental Disorders (BNBD-NDD).